Cu-Se-based high-entropy thermoelectric material capable of inhibiting Cu ion migration and preparation method of Cu-Se-based high-entropy thermoelectric material

By accurately controlling the element proportion and particle size distribution of Cu-Se-based high-entropy thermoelectric materials, suppressing Cu ion migration and optimizing the material structure, the problems of poor mechanical properties and insufficient high temperature stability of Cu2Se materials are solved, and its thermoelectric properties and mechanical properties are improved Performance, achieving higher ZT values ​​and durability.

CN119300694APending Publication Date: 2025-01-10QINGHAI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411204902.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

As a temperature-differential electrical material, copper selenium (Cu2Se) has poor mechanical properties and insufficient high-temperature stability, resulting in poor performance in practical applications and high-temperature environments.

Method used

By accurately controlling the element molar ratio and particle size distribution of Cu-Se-based high-entropy thermoelectric materials, a more stable lattice structure is formed, which inhibits the migration of Cu ions, and optimizes carrier concentration and conductivity by adjusting the composition and structure of the material. , Seebeck coefficient and thermal conductivity to improve the ZT value and mechanical properties of the material.

Benefits of technology

The structural integrity and long-term stability of Cu-Se-based high-entropy thermoelectric material are achieved, which significantly improves its thermoelectric conversion efficiency and mechanical properties at high temperatures, and enhances the durability and chemical stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300694A_ABST
    Figure CN119300694A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu-Se-based high-entropy thermoelectric material capable of inhibiting Cu ion migration and a preparation method of the Cu-Se-based high-entropy thermoelectric material, and belongs to the technical field of high-entropy thermoelectric materials. The general formula of the Cu-Se-based high-entropy thermoelectric material is Cux (Pb < 1-y > M < y >) (InzSn < 1-z >) SemTn, x is equal to 1.2-1.8, y is equal to 0.2-0.8, z is equal to 0.1-0.3, m is equal to 0.4-0.9, n is equal to 0.1-0.15, and x, y, z, m and n are molar molecule numbers. The Cu-Se-based high-entropy thermoelectric material can form a more stable lattice structure by accurately controlling the molar ratio and particle size distribution of the elements, so that migration of Cu ions under high current or temperature gradient is inhibited, and the structural integrity and long-term stability of the material can be maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high entropy thermoelectric materials, and in particular relates to a Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration and a preparation method thereof. Background Art

[0002] Thermoelectric materials are also called thermoelectric materials. They are mainly used to prepare thermoelectric refrigeration devices and thermoelectric power generation devices. The performance of thermoelectric materials mainly depends on the dimensionless thermoelectric figure of merit ZT of the material, which is defined as: ZT = S 2 σT / κ, where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature. The higher the ZT value, the higher the power generation and cooling efficiency of the corresponding device.

[0003] Copper selenium alloy Cu2Se is a kind of excellent medium temperature thermoelectric material with high electrical conductivity and low thermal conductivity. + It can move in the sublattice formed by Se, which is called "phonon glass-electron crystal". Due to this characteristic, when a large current passes through, it will cause Cu + Irreversible migration causes the collapse of the material structure, so it is necessary to dope some metal elements to form high entropy thermoelectric materials to suppress Cu + Harmful migration, currently mechanical alloying or vacuum melting combined with hot pressing sintering or SPS synthesis is usually used. The problem is that the quartz tube needs to be carbon coated during the vacuum melting process. Otherwise, due to the low vapor pressure of selenium, it will evaporate rapidly at high temperature and fill the entire quartz tube, which may cause the quartz tube to burst; mechanical alloying has the disadvantages of low efficiency and high requirements for ball mills. + The strong ionicity exhibited results in low electrical conductivity, low Seebeck coefficient and low ZT value of the material. Therefore, the key is to use added elements to synthesize high-entropy thermoelectric materials to improve the electrical properties of the material.

[0004] Cu2Se-based bulk materials are synthesized through high-pressure technology and attempts are made to find corresponding solutions. On the one hand, high-pressure synthesis technology can directly synthesize element powders into bulk compounds, which is simple to operate, time-saving, and produces pure products, providing a possibility for solving the above-mentioned material preparation problems. On the other hand, high pressure provides a high-pressure sealed environment for the synthesis cavity, which can inhibit the evaporation of Se elements. By optimizing the high-pressure synthesis process, Cu metal deposition can be inhibited, providing a new idea for solving the stability problem of Cu2Se-based bulk materials.

[0005] Copper selenium (Cu2Se) as a thermoelectric material has certain advantages, such as high thermoelectric performance. The use of high-pressure technology to synthesize copper selenium also solves the problem of quartz tube explosion caused by low vapor pressure of selenium. However, Cu2Se also has its limitations and disadvantages, including:

[0006] (1) The poor mechanical properties of Cu2Se limit its durability in practical applications;

[0007] (2) Cu2Se has poor stability at high temperatures, especially in oxidizing or corrosive environments. Summary of the invention

[0008] The purpose of the present invention is to provide a Cu-Se based high entropy thermoelectric material and a preparation method capable of inhibiting the migration of Cu ions, so as to solve the problem that the above copper selenium as a thermoelectric material has poor mechanical properties and poor high temperature stability. The present invention can form a more stable lattice structure by precisely controlling the molar ratio and particle size distribution of each element, thereby inhibiting the migration of Cu ions under high current or temperature gradient, and helping to maintain the structural integrity and long-term stability of the material.

[0009] To achieve the above object, the present invention provides a Cu-Se based high entropy thermoelectric material capable of inhibiting the migration of Cu ions. The general formula of the Cu-Se based high entropy thermoelectric material is Cu x (Pb 1-y M y )(In z Sn 1-z )Se m T n , x=1.2~1.8, y=0.2~0.8, z=0.1~0.3, m=0.4~0.9, n=0.1~0.15, wherein x, y, z, m, n are the molar molecular numbers.

[0010] Preferably, M is one or more of Mn, Fe, Co, Ni, and Zn.

[0011] Preferably, T is one or more of S, Br, and I.

[0012] As a high entropy thermoelectric material, traditional Cu2Se will cause Cu +Irreversible migration causes the collapse of the material structure. Usually, the migration of copper ions is limited by doping with other metals to form a stable microstructure. However, the presence of doped metal elements causes the high-temperature performance of the material to deteriorate. The doped metal is unevenly distributed in the Cu2Se matrix, affecting the electrical conductivity and thermal conductivity of the material, causing local chemical imbalance and forming defects. The present invention can optimize the carrier concentration, electrical conductivity, Seebeck coefficient and thermal conductivity by adjusting the composition and structure of the material. Specifically, the ratio of Cu, Pb, M, In, Sn and T and the selection of M and T elements can regulate the electronic structure of the material, thereby affecting the properties of the carriers and ultimately improving the ZT value of the material. The addition and proportion changes of elements such as Cu, Pb, In, Sn in the present invention can regulate the type and concentration of carriers. The addition of In and Sn can introduce additional carriers, thereby increasing electrical conductivity. The presence of Cu helps to improve the electrical conductivity of the material because Cu is an excellent electronic conductor. The present invention can optimize the Seebeck coefficient (S) value by adjusting the band structure of the material. The introduction of Se element can adjust the band structure of the material, affect the effective mass of the carrier, and thus affect the S value. The incorporation of M elements (such as Mn, Fe, Co, Ni, Zn) can also improve the S value by changing the electronic structure of the material. The incorporation of M elements can increase the phonon scattering center, increase the scattering probability of phonons by destroying the lattice periodicity, and thus reduce the lattice thermal conductivity. The synergistic effect of Se and other elements (Cu, Pb, In, Sn) can further optimize the thermoelectric performance. Se can not only improve electrical conductivity, but also improve the S value by adjusting the band structure, and the synergistic effect with other elements can further reduce thermal conductivity. The addition of In and Sn can increase the carrier concentration of the material, and the incorporation of M elements can reduce thermal conductivity. The synergistic effect of the two can significantly improve the ZT value.

[0013] The present invention can optimize the electronic structure of the material, improve the carrier concentration and mobility, enhance the electrical conductivity and Seebeck coefficient, and reduce the thermal conductivity by comprehensively adjusting the ratio of Cu, Pb, M, In, Sn and T, as well as the selection of M and T elements. The goal of this comprehensive optimization is to create an ideal balance point in the material to maximize the ZT value, thereby improving the thermoelectric conversion efficiency.

[0014] Preferably, x / y=1.5-3;

[0015] Cu is a composite of copper with a particle size of 3 to 5 μm, a particle size of 10 to 20 μm, and a particle size of 30 to 50 μm in a weight ratio of 1:0.5 to 0.8:0.1 to 0.3;

[0016] Pb is a lead compound of a particle size of 500-800 nm, a particle size of 1-5 μm, and a particle size of 20-30 μm in a weight ratio of 0.4-0.6:0.8-1.2:1.5-2.0;

[0017] M is a compound of particles with a particle size of 1 to 3 μm, a particle size of 5 to 15 μm and a particle size of 30 to 40 μm in a weight ratio of 1.2 to 1.4:0.3 to 0.5:0.8 to 1.0.

[0018] Preferably, x / z=5-10;

[0019] In is a compound of indium with a particle size of 100 to 200 nm, a particle size of 5 to 10 μm, and a particle size of 20 to 40 μm in a weight ratio of 0.5 to 0.8:1 to 1.5:0.2 to 0.4;

[0020] Sn is a composite of tin with a particle size of 200-500 nm, a particle size of 1-3 μm and a particle size of 5-8 μm in a weight ratio of 1.5-2:1-1.3:0.5-0.8.

[0021] Preferably, m / n=3-6.

[0022] Each element in the present invention has its specific role, as follows:

[0023] Cu element: Cu is a good electronic conductor. Increasing the molar ratio of Cu helps to improve the conductivity σ. At the same time, a moderate excess of Cu helps to inhibit the migration of Cu ions and maintain the stability of the material structure, thereby indirectly improving the ZT value.

[0024] Pb and M elements: The presence of Pb can provide additional electrons, while the incorporation of M elements (such as Mn, Fe, Co, Ni, and Zn) can act as scattering centers to reduce the lattice thermal conductivity κ. At the same time, by destroying the lattice periodicity and increasing phonon scattering, κ can be further reduced and the ZT value can be increased.

[0025] In and Sn elements: In and Sn can optimize the carrier concentration. In acts as a p-type dopant and Sn acts as an n-type dopant. The two can work together to adjust the carrier type and concentration of the material, thereby optimizing the conductivity σ and Seebeck coefficient S.

[0026] Se and T elements: Se is an important component in thermoelectric materials, which can optimize the band structure and increase the S value. The addition of T elements (S, Br, I) can further reduce the thermal conductivity κ and may increase the S value by affecting the band structure.

[0027] Although the present invention designs Cu, Pb, M, In, Sn, Se, and T elements in the high entropy thermoelectric material, which significantly improves the ZT value of the material, its high temperature stability and mechanical properties are insufficient and need to be further improved. The present invention continues to develop and find that further limiting the content (x / y) of copper, lead and metal M, the content (x / z) of copper, indium, tin, and the content (m / n) of selenium and T elements can significantly improve its high temperature stability. In thermoelectric materials, the migration of Cu ions can lead to instability of the material structure, especially at high temperatures. By adjusting the ratio of Cu to other elements (x / y=1.5-3), a more stable lattice structure can be formed, reducing the migration of Cu ions, thereby maintaining the structural integrity and performance stability of the material at high temperatures. The specific ratio of Cu, Pb and M elements can promote the formation of a complex high entropy alloy lattice structure. This structure has high chemical stability, can resist structural changes even at high temperatures, maintain the integrity of the lattice, and thus maintain thermoelectric performance.

[0028] At high temperatures, materials are susceptible to oxidation and corrosion. The present invention can form a more stable lattice structure by adjusting the ratio of Cu to In and Sn (x / z=5-10), inhibiting the migration of Cu ions, thereby improving the structural stability of the material and the durability of the thermoelectric performance. The addition of Se and T elements (especially Br and I) can form more stable compounds, enhance the chemical stability of the material, reduce oxidation and corrosion at high temperatures, and thus improve the long-term working stability of the material. The presence of Se and T elements can help form a more complex lattice structure, which can inhibit the migration of Cu ions at high temperatures and maintain the structural integrity and performance stability of the material. The specific ratio of Se and T elements can improve the thermal stability of the material, which means that the performance of the material decreases more slowly under high temperature conditions and can withstand higher operating temperatures without losing its thermoelectric properties.

[0029] The inventors continued to research and develop and found that by designing the type of elements and the ratio between the elements, although the dimensionless thermoelectric figure of merit and high temperature resistance of high entropy thermoelectric materials have been solved, the mechanical properties of high entropy thermoelectric materials can be further improved. The present invention limits the particle size of each metal element. Element particles of different particle sizes can promote a more uniform microstructure and avoid microscopic defects caused by large particles, such as cracks and holes, thereby improving the mechanical strength and toughness of the material. In addition, the mixing of different particle sizes can increase the phonon scattering inside the material, which helps to reduce the lattice thermal conductivity and further improve the ZT value. The present invention can improve the microstructure of the material by controlling the particle size distribution of Cu, Pb and M elements, increase the number of grain boundaries and interfaces, thereby improving the hardness, toughness and creep resistance of the material. The improvement of these mechanical properties is crucial for the stable operation of the material at high temperatures. The present invention can improve the mechanical properties of the material, such as hardness and toughness, by controlling the particle size distribution of Cu, Sn and In, which is very important for the mechanical stability and durability of the material under high temperature conditions, and prevents the material from mechanical failure during thermal cycles.

[0030] A second aspect of the present invention provides a method for preparing a Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration, comprising the following steps:

[0031] (1) Under argon protective atmosphere, according to Cu x (Pb 1-y M y )(In z Sn 1-z )Se m T n The general formula is as follows: weighing various raw materials and mixing them, and then ball milling them to obtain mixed powder;

[0032] (2) drying the mixed powder and cold pressing it in a molybdenum cup to obtain a first compact;

[0033] (3) crushing the first compact to less than 50 μm in a crusher, and then cold pressing in a molybdenum cup to obtain a second compact;

[0034] (4) Sintering the second compact to obtain a Cu-Se based high entropy thermoelectric material.

[0035] Preferably, in step (1), the ball milling speed is 400-600 rpm, and the ball milling time is 10-15 h.

[0036] Preferably, the drying temperature in step (2) is 80-100° C., and the pressure of cold pressing in steps (2) and (3) is 6-10 MPa.

[0037] Preferably, the sintering process in step (4) is constant temperature sintering at 600-900° C. for 2-10 minutes at 2-6 GPa, or spark plasma sintering;

[0038] The conditions of spark plasma sintering are: heating rate of 100-150°C / min, sintering temperature of 600-900°C, sintering pressure of 40-85MPa, and holding time of 15-20min.

[0039] Therefore, the present invention adopts the above-mentioned Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration and the preparation method, which has the following beneficial effects:

[0040] 1. By precisely controlling the molar ratio and particle size distribution of each element, the Cu-Se based high entropy thermoelectric material can form a more stable lattice structure, thereby inhibiting the migration of Cu ions under high current or temperature gradient, and helping to maintain the structural integrity and long-term stability of the material.

[0041] 2. The present invention can optimize the carrier concentration, electrical conductivity, Seebeck coefficient and thermal conductivity by adjusting the composition and structure of the material. Specifically, the ratio of Cu, Pb, M, In, Sn and Tn and the selection of M and T elements can regulate the electronic structure of the material, thereby affecting the properties of the carriers and ultimately improving the ZT value of the material. The incorporation of the M element can increase the phonon scattering center and reduce the lattice thermal conductivity, while the synergistic effect of Se and other elements can improve the electrical conductivity and Seebeck coefficient.

[0042] 3. The microstructure of the material directly affects its macroscopic performance. The present invention can promote the uniform dispersion of the components in the material by controlling the particle size distribution and weight ratio of different elements, forming a more ordered and stable lattice structure. This optimized microstructure reduces microscopic defects, improves the electrical conductivity and thermal stability of the material, and reduces thermal conductivity, which helps to improve thermoelectric performance.

[0043] 4. The mechanical stability and durability of thermoelectric materials are crucial in practical applications. The present invention can improve the mechanical properties of materials by controlling the particle size distribution and element ratio, ensuring that the materials can maintain functional integrity under various mechanical stresses and deformations, and the materials have the advantage of maintaining long-term operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is an electron microscope image of the high entropy thermoelectric material prepared in Example 1. DETAILED DESCRIPTION

[0045] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.

[0046] All raw materials used in the examples and comparative examples were purchased.

[0047] Example 1

[0048] This embodiment provides a Cu-Se based high entropy thermoelectric material capable of inhibiting the migration of Cu ions. The general formula of the Cu-Se based high entropy thermoelectric material is Cu x (Pb 1-y M y )(In z Sn 1-z )Se m T n , x=1.2, y=0.6, z=0.2, m=0.5, n=0.12, where x, y, z, m, n are the molar numbers of molecules.

[0049] M represents Co and Ni, and the molar molecular numbers of Co and Ni are 1:1.

[0050] T is Br.

[0051] x / y=2;

[0052] Cu is a copper compound of 5 μm, 10 μm and 30 μm in a weight ratio of 1:0.6:0.2;

[0053] Pb is a lead compound of 600nm, 3μm and 25μm in weight ratio of 0.5:1.0:1.5;

[0054] M (Ni, Co) is a compound of M with a particle size of 3 μm, a particle size of 15 μm and a particle size of 40 μm in a weight ratio of 1.2:0.5:1.0.

[0055] x / z=6;

[0056] In is a compound of indium with a particle size of 150 nm, a particle size of 8 μm, and a particle size of 30 μm in a weight ratio of 0.6:1.2:0.3;

[0057] Sn is a composite of tin with a particle size of 300 nm, a particle size of 2 μm and a particle size of 6 μm in a weight ratio of 1.8:1.2:0.6.

[0058] m / n=4.17.

[0059] This embodiment also provides a method for preparing a Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration, comprising the following steps:

[0060] (1) Under argon protective atmosphere, according to Cu x (Pb 1-y M y )(Inz Sn 1-z )Se m T n The raw materials were weighed and mixed, and then ball-milled to obtain mixed powder; the ball-milling speed was 500 rpm, and the ball-milling time was 12 h.

[0061] (2) drying the mixed powder and then cold pressing the mixed powder in a molybdenum cup to obtain a first compact; the drying temperature is 80° C. and the cold pressing pressure is 9 MPa.

[0062] (3) The first compact was crushed to 50 μm in a crusher and then cold pressed in a molybdenum cup to obtain a second compact; the cold pressing pressure was 9 MPa.

[0063] (4) Sintering the second compact to obtain a Cu-Se based high entropy thermoelectric material; the sintering process is performed at a constant temperature of 700° C. for 10 minutes under 6 GPa.

[0064] Figure 1 This is the SEM image of the high entropy thermoelectric material prepared in this example.

[0065] Example 2

[0066] The difference between this embodiment and embodiment 1 is: the general formula of Cu-Se based high entropy thermoelectric material.

[0067] The general formula of the Cu-Se based high entropy thermoelectric material in this embodiment is Cu x (Pb 1-y M y )(In z Sn 1-z )Se m T n , x = 1.8, y = 0.6, z = 0.2, m = 0.5, n = 0.1, where x, y, z, m, n are the number of moles;

[0068] M is Fe and Zn, and the molar number of Fe and Zn is 1:1;

[0069] T is Br;

[0070] x / y=3;

[0071] x / z=9;

[0072] m / n=5.

[0073] Example 3

[0074] The difference between this embodiment and embodiment 1 is: The difference between this embodiment and embodiment 1 is: the general formula of Cu-Se based high entropy thermoelectric material.

[0075] The general formula of the Cu-Se based high entropy thermoelectric material in this embodiment is Cu x (Pb 1-y M y )(In z Sn 1-z )Se m T n , x = 1.6, y = 0.8, z = 0.3, m = 0.6, n = 0.15, where x, y, z, m, n are the number of moles;

[0076] M is Mn;

[0077] T is S and I, and the molar number of S and I is 1:1;

[0078] x / y=2;

[0079] x / z=5.33;

[0080] m / n=4.

[0081] Example 4

[0082] The difference between this embodiment and embodiment 1 is that the sintering process in step (4) is spark plasma sintering, and the conditions of spark plasma sintering are: heating rate of 100°C / min, sintering temperature of 800°C, sintering pressure of 65MPa, and holding time of 20min.

[0083] Comparative Example 1

[0084] The difference between this comparative example and Example 1 is: y=0.2, x / y=6.

[0085] Comparative Example 2

[0086] The difference between this comparative example and Example 1 is: z=0.1, x / z=12.

[0087] Comparative Example 3

[0088] The difference between this comparative example and Example 1 is: m=0.9, m / n=7.5.

[0089] Comparative Example 4

[0090] The difference between this comparative example and Example 1 is: y=0.1, x / y=12.

[0091] Comparative Example 5

[0092] The difference between this comparative example and Example 1 is: z=0.8, x / z=1.5.

[0093] Comparative Example 6

[0094] The difference between this comparative example and Example 1 is: m=0.1, m / n=0.83.

[0095] Comparative Example 7

[0096] The difference between this comparative example and Example 1 is that Cu is a compound of copper with a particle size of 10 μm, a particle size of 50 μm and a particle size of 100 μm in a weight ratio of 1:1:1.

[0097] Comparative Example 8

[0098] The difference between this comparative example and Example 1 is that Pb is a compound of lead with a particle size of 1 μm, a particle size of 10 μm and a particle size of 50 μm in a weight ratio of 1:1:1.

[0099] Comparative Example 9

[0100] The difference between this comparative example and Example 1 is that M is a compound of M with a particle size of 5 μm, a particle size of 30 μm and a particle size of 50 μm in a weight ratio of 1:1:1.

[0101] Comparative Example 10

[0102] The difference between this comparative example and Example 1 is that In is a compound of indium with a particle size of 500 nm, a particle size of 1 μm and a particle size of 10 μm in a weight ratio of 1:1:1.

[0103] Comparative Example 11

[0104] The difference between this comparative example and Example 1 is that Sn is a compound of tin with a particle size of 1 μm, a particle size of 10 μm and a particle size of 20 μm in a weight ratio of 1:1:1.

[0105] Performance Testing

[0106] (1) The conductivity and Seebeck coefficient of the high entropy thermoelectric materials of the embodiments and comparative examples were measured using a comprehensive thermoelectric performance tester (ZEM-3) at a test temperature of 30-600°C (303-873K), where σ and S represent the conductivity and Seebeck coefficient, respectively.

[0107] The thermal diffusion coefficient of the high entropy thermoelectric materials of this embodiment and the comparative example was measured using a laser thermal conductivity analyzer (LFA), and then converted into thermal conductivity, where κ represents the thermal conductivity.

[0108] According to the test results of σ, S and κ, the dimensionless thermoelectric figure of merit (ZT value) of the high entropy thermoelectric material can be converted. The ZT values ​​of the embodiments and comparative examples at 600°C are shown in Table 1.

[0109] Table 1 Thermoelectric performance test results at 600℃

[0110]

[0111]

[0112] It can be seen from the above performance test results that the thermoelectric performance of Examples 1-4 is excellent, especially the comprehensive performance of Example 1 is the most outstanding. This is mainly because the molar ratio and particle size distribution of each element are precisely controlled in Example 1, and the Cu-Se-based high entropy thermoelectric material can form a more stable lattice structure, thereby inhibiting the migration of Cu ions under high current or temperature gradient, which helps to maintain the structural integrity and long-term stability of the material.

[0113] However, the comparative examples are significantly worse than the embodiments in terms of corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the addition ratio of lead and metal M in the high-entropy thermoelectric material is changed. It can be seen that the thermoelectric performance has obviously decreased, proving that the addition amount of metal elements has an important influence on the thermoelectric performance. In comparative example 2, the addition ratio of indium and tin in the high-entropy thermoelectric material is changed. It can be seen that the thermoelectric performance has also decreased, indicating that the addition amount of metal elements has an influence on the thermoelectric performance. Only in a specific ratio can several metal elements optimize the electronic structure of the material, increase the carrier concentration and mobility, enhance the electrical conductivity and Seebeck coefficient, and reduce the thermal conductivity. In comparative example 3, the addition amount of the non-metallic element selenium is changed, and the thermoelectric performance also decreases, indicating that the comprehensive optimization of non-metallic elements and metal elements to create an ideal balance point in the material can maximize the ZT value, thereby improving the thermoelectric conversion efficiency. Comparative Examples 4-7 change the addition ratio of metal elements and non-metallic elements, and the addition ratio is not within the prescribed range of the present invention. At the same time, the ratio between the elements (x / y, x / z, m / n) is also not within the prescribed range of the present invention. Compared with Comparative Examples 1-3, only the addition ratio of metal elements and non-metallic elements is changed, and the ratio between the elements (x / y, x / z, m / n) is still within the prescribed range of the present invention. The thermoelectric performance of the high entropy thermoelectric material prepared in Comparative Examples 4-7 is further reduced, indicating that only under the element addition ratio in the present invention, the thermoelectric conversion efficiency of the high entropy thermoelectric material can be achieved. Comparative Examples 7-11 changed the particle size of the metal element, and found that the thermoelectric performance of the high entropy thermoelectric material prepared therefrom decreased, indicating that the particle size distribution of the metal element will affect the lattice structure of the material, resulting in a decrease in thermoelectric performance. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0114] (2) The mechanical properties of the embodiments and comparative examples were tested, and the hardness of the samples was measured using Vickers hardness measurement. The test results are shown in Table 2.

[0115] Table 2 Mechanical properties test results

[0116] Hardness / MPa Example 1 625 Example 2 613 Example 3 620 Example 4 606 Comparative Example 1 550 Comparative Example 2 541 Comparative Example 3 528 Comparative Example 4 482 Comparative Example 5 460 Comparative Example 6 457 Comparative Example 7 471 Comparative Example 8 428 Comparative Example 9 435 Comparative Example 10 440 Comparative Example 11 449

[0117] As can be seen from Table 2, the hardness of Examples 1-4 is relatively high, indicating that the high entropy thermoelectric material prepared by the present invention has both high thermoelectric performance and mechanical properties, while in the high entropy thermoelectric material prepared by Comparative Examples 1-3, the ratio (x / y) between the copper addition and the M metal addition, the ratio (x / z) between the copper addition and the tin metal addition, and the ratio (m / n) between the Se addition and the T addition respectively change, which is not within the scope defined by the present invention, resulting in a decrease in the hardness of the high entropy thermoelectric material and a deterioration in mechanical properties. Comparative Examples 4-7 further adjust the addition ratio of metal elements (M metal, Pb, In, Sn) and non-metallic elements (Se), and the limited addition ratio of metal elements and non-metallic elements exceeds the scope defined by the present invention. At the same time, the addition ratio of each element is also not within the scope defined by the present invention. The hardness of the prepared high entropy thermoelectric material is further reduced, and the mechanical properties are deteriorated, indicating that the addition amount of the elements defined in the present invention and the addition ratio between the elements have a very important influence on the mechanical properties of the high entropy thermoelectric material. Comparative Examples 7-11 adjusted the particle size distribution of the elements, and found that compared with the embodiments, the hardness of the high entropy thermoelectric materials prepared in Comparative Examples 7-11 decreased to varying degrees, indicating that the particle size distribution of metal elements will also affect the performance of high entropy thermoelectric materials.

[0118] Therefore, the present invention adopts a Cu-Se based high entropy thermoelectric material and a preparation method of the above structure that can inhibit the migration of Cu ions. By precisely controlling the molar ratio and particle size distribution of each element, the Cu-Se based high entropy thermoelectric material can form a more stable lattice structure, thereby inhibiting the migration of Cu ions under high current or temperature gradient, which helps to maintain the structural integrity and long-term stability of the material.

[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration, characterized in that: The general formula of Cu-Se based high entropy thermoelectric materials is Cu x (Pb 1-y M y )(In z Sn 1-z )Se m T n , x=1.2~1.8, y=0.2~0.8, z=0.1~0.3, m=0.4~0.9, n=0.1~0.15, wherein x, y, z, m, n are the molar molecular numbers.

2. The Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration according to claim 1, characterized in that: M is one or more of Mn, Fe, Co, Ni, and Zn.

3. The Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration according to claim 1, characterized in that: T is one or more of S, Br, and I.

4. The Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration according to claim 1, characterized in that: x / y=1.5-3; Cu is a composite of copper with a particle size of 3 to 5 μm, a particle size of 10 to 20 μm, and a particle size of 30 to 50 μm in a weight ratio of 1:0.5 to 0.8:0.1 to 0.3; Pb is a lead compound of a particle size of 500-800 nm, a particle size of 1-5 μm, and a particle size of 20-30 μm in a weight ratio of 0.4-0.6:0.8-1.2:1.5-2.0; M is a compound of particles with a particle size of 1 to 3 μm, a particle size of 5 to 15 μm and a particle size of 30 to 40 μm in a weight ratio of 1.2 to 1.4:0.3 to 0.5:0.8 to 1.

0.

5. The Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration according to claim 1, characterized in that: x / z=5-10; In is a compound of indium with a particle size of 100 to 200 nm, a particle size of 5 to 10 μm, and a particle size of 20 to 40 μm in a weight ratio of 0.5 to 0.8:1 to 1.5:0.2 to 0.4; Sn is a composite of tin with a particle size of 200-500 nm, a particle size of 1-3 μm and a particle size of 5-8 μm in a weight ratio of 1.5-2:1-1.3:0.5-0.

8.

6. The Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration according to claim 1, characterized in that: m / n=3~6.

7. A method for preparing a Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Under argon protective atmosphere, according to Cu x (Pb 1-y M y )(In z Sn 1-z )Se m T n The general formula is as follows: weighing various raw materials and mixing them, and then ball milling them to obtain mixed powder; (2) drying the mixed powder and cold pressing it in a molybdenum cup to obtain a first compact; (3) crushing the first compact to less than 50 μm in a crusher, and then cold pressing in a molybdenum cup to obtain a second compact; (4) Sintering the second compact to obtain a Cu-Se based high entropy thermoelectric material.

8. The method for preparing a Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration according to claim 7, characterized in that: In step (1), the ball milling speed is 400-600 rpm, and the ball milling time is 10-15 h.

9. The method for preparing a Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration according to claim 7, characterized in that: The drying temperature in step (2) is 80-100° C., and the cold pressing pressure in steps (2) and (3) is 6-10 MPa.

10. The method for preparing a Cu-Se based high entropy thermoelectric material capable of inhibiting Cu ion migration according to claim 7, characterized in that: The sintering process in step (4) is constant temperature sintering at 600-900° C. for 2-10 minutes at 2-6 GPa, or spark plasma sintering; The conditions of spark plasma sintering are: heating rate of 100-150°C / min, sintering temperature of 600-900°C, sintering pressure of 40-85MPa, and holding time of 15-20min.